Laparoscopic rectal dissection preserves erectile function after ileal pouch–anal anastomosis: a two‐centre study. (28th October 2020) - Picaud, Olivier; Beyer‐Berjot, Laura; Parc, Yann; Karsenty, Gilles; Creavin, Ben; Berdah, Stéphane; Lefevre, Jérémie H.
Abstract: Aim: Few studies have been published on erectile function after ileal pouch–anal anastomosis (IPAA) and, unlike in women, male fertility after IPAA has never been assessed. The primary objective was to assess the impact of IPAA on erectile function. The secondary objective was to assess the impact of IPAA on male fertility. Methods: All of the male patients who underwent IPAA in two university care centres between 2003 and 2017, aged 70 years or less at the time of operation, were included. Forty‐eight per cent of the patients responded to the international index of erectile function, the Jorge–Wexner score and a fertility questionnaire. All demographic and perioperative data were prospectively collected. Fertility results were compared with those of a control group undergoing appendectomy, matched for age at the time of operation, desire for paternity and length of follow‐up. Results: One hundred and thirty‐nine patients were included, among which 46 (33%) presented with erectile dysfunction and 14 (10%) with severe erectile dysfunction. Age older than 50 years (OR 0.27, 95% CI 0.12–0.62, P  = 0.002) and rectal dissection performed by open surgery (OR 4.16, 95% CI 1.62–10.65, P  = 0.003) were independent risk factors for erectile dysfunction. There was no infertility after IPAA compared with controls: indeed, 23 (16%) IPAA patients presented with pregnancy in their couple versus 27 (22%) controls ( P  = 0.29), whereas 36 (26%) IPAA patients and 34 (28%) controls ( P  = 0.80) expressed paternity desire. Conclusion: A total laparoscopic approach, including rectal dissection, should be preferred to preserve erectile function. Male fertility is not impaired after IPAA.